The Influence of Work-Family Conflict and Work-Life Balance on Organizational Citizenship Behavior Among Nurses at Waled Regional General Hospital - Ahmad Nadhir; Lisa Harry Sulistiyowati (Interdisciplinary Social Studies, 2026)
This study aims to analyze the influence of Work Family Conflict and Work Life Balance on Organizational Citizenship Behavior (OCB) in nurses at Waled Hospital, Cirebon Regency, both partially and simultaneously. The population in this study is inpatient nurses at Waled Hospital Cirebon Regency who are married and have a minimum working period of five years, with a population of 132 nurses who are married and have worked for more than 5 years. The sample was determined using the Slovin formula so that a sample of 100 respondents was obtained. Data collection was carried out through a questionnaire with a Likert scale, while the data analysis used simple linear regression and multiple linear regression with the help of the IBM SPSS version 26 program. The results showed that Work Family Conflict had a negative and significant effect on Organizational Citizenship Behavior, which was evidenced by a t-value of ?2.298 and a significance level of 0.024 (< 0.05). Work Life Balance also had a significant effect on Organizational Citizenship Behavior, with a calculated t-value of ?4,400 and a significance level of 0.000 (< 0.05). Simultaneously, Work Family Conflict and Work Life Balance had a significant effect on Organizational Citizenship Behavior, which was shown by an F value of 120.666 with a significance level of 0.000 (< 0.05). A determination coefficient value (R²) of 0.713 showed that 71.3% of the variation in Organizational Citizenship Behavior could be explained by Work Family Conflict and Work Life Balance, while the rest were influenced by other factors outside the study. This study emphasizes the importance of managing role conflicts and improving work-life balance in encouraging nurses' voluntary work behavior to support the effectiveness of hospital organizations.